Mexico : 2021 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
Spurred by strong U.S. growth and rising vaccination rates, the economy is rebounding. The government has successfully maintained external, financial, and fiscal stability despite the deepest recession in decades. Nonetheless, Mexico is bearing a very heavy humanitarian, social, and economic cost from COVID-19, including over half a million excess deaths, sizable under-employment, an increase in already-high levels of poverty, and learning losses for the young. Real income per capita is continuing its long-run divergence from the U.S., while additional challenges are emerging from technological shifts and climate change.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy